AN ANALYSIS OF NEW WORDS IN REALITY SHOW: SOCIOLINGUISTIC PERSPECTIVE - Agustien , Najwa Septya; Mulatsih, Devi (Cirebon International Conference on Education and Economics Proceeding, 2024)
Even though New Words has been the subject of numerous studies, none of them have systematically investigated the types of new words found and the social factors used by the speaker in the reality TV show. This reality TV shows-based research, framed within the concept of Morphology as a result of the spread of English as a global language, proposes an instructional design for sociolinguistics learning mediated by YouTube as a virtual platform. The method is using qualitative. The data sources are from various reality TV shows from Net TV, Trans TV, and Trans 7. The results of the research are founds some new words such as: Baper, E-Commerce, Ambyar, Gemoy, FYP, Pargoy, Ghosting, and so on, while the factors affected using new words by speakers because of Geographical Dialect, Linguistics Innovations, Social Group Influence, Globalization Influence, and Development of Technology and Science.